2022
DOI: 10.1155/2022/3450207
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Strategies for Ischemic Stroke: Recent Insights into Autophagy

Abstract: Stroke is one of the leading causes of death and disability worldwide. Autophagy is a conserved cellular catabolic pathway that maintains cellular homeostasis by removal of damaged proteins and organelles, which is critical for the maintenance of energy and function homeostasis of cells. Accumulating evidence demonstrates that autophagy plays important roles in pathophysiological mechanisms under ischemic stroke. Previous investigations show that autophagy serves as a “double-edged sword” in ischemic stroke as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 174 publications
(174 reference statements)
0
19
0
Order By: Relevance
“…Autophagy plays a significant role in IS . On the one hand, inflammasome activation can alleviate cerebral ischemic injury by disrupting autophagy activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy plays a significant role in IS . On the one hand, inflammasome activation can alleviate cerebral ischemic injury by disrupting autophagy activation.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a significant role in IS. 21 On the one hand, inflammasome activation can alleviate cerebral ischemic injury by disrupting autophagy activation. On the other hand, autophagy activation inhibits ischemia-caused neuroinflammation and serves as a cellular protective mechanism, while inflammation is a defense mechanism, both of which jointly respond to ischemic brain damage.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that autophagy is involved in the death of various cells after stroke [ 5 - 7 ], including microglia [ 8 - 9 ]. However, the role and potential mechanisms of microglial autophagy in ischemic stroke after CEA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have been conducted recently in the field of stroke management, 43 focusing on topics such as early recognition, 44 , 45 , 46 , 47 , 48 novel therapeutics, 49 , 50 , 51 comparison of thrombolytic agents, 52 combination of MT with IVT, 53 and safety and efficacy of IVT after antagonization of unfractionated heparin with protamine, 54 among others. This review critically assesses IVT versus MT within a 4.5‐h window, considering pretreatment and posttreatment NIHSS scales—an aspect overlooked in current literature.…”
Section: Introductionmentioning
confidence: 99%